1998
DOI: 10.1029/1998gl900147
|View full text |Cite
|
Sign up to set email alerts
|

Doubled CO2 effects on NOy in a coupled 2D model

Abstract: Abstract.Stratospheric NOy fields calculated using a zonally averaged interactive chemistry-radiation-dynamics model show significant sensitivity to the model CO2. Modeled upper stratospheric NOy decreases by about 15% in response to CO2 doubling, mainly due to the temperature decrease calculated to result from increased CO2 cooling. The abundance of atomic nitrogen, N, increases because the rate of the strongly temperature dependent reaction N + 02 -• NO + O decreases at lower temperatures. Increased N leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 11 publications
2
50
0
Order By: Relevance
“…Their findings are consistent with our observations at Jungfraujoch: they showed that the NO 2 /NO partitioning is currently changing with time to favor NO, due to stratospheric cooling, which slows the NO + O 3 → NO 2 + O 2 reaction, and decreasing ClO concentrations, which slows the NO + ClO → NO 2 + Cl reaction. It should be noted that a stratospheric cooling can also decrease the amount of NO y in the stratosphere from N 2 O (Rosenfield and Douglass, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Their findings are consistent with our observations at Jungfraujoch: they showed that the NO 2 /NO partitioning is currently changing with time to favor NO, due to stratospheric cooling, which slows the NO + O 3 → NO 2 + O 2 reaction, and decreasing ClO concentrations, which slows the NO + ClO → NO 2 + Cl reaction. It should be noted that a stratospheric cooling can also decrease the amount of NO y in the stratosphere from N 2 O (Rosenfield and Douglass, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the sink for NO x is temperature dependent, so CO 2 -induced cooling of the stratosphere decreases NO x abundances by slowing the highly temperature-dependent Reaction (R1) (below). The subsequent increase in N leads to an increase in the rate of Reaction (R2), therefore decreasing NO x abundances (Rosenfield and Douglass, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The former is strongly influenced by cooling of the stratosphere (Rosenfield and Douglass, 1998) and by changes in the strength of the BDC (Cook and Roscoe, 2012).…”
Section: Changes In No X Destruction Ratesmentioning
confidence: 99%